Principles of implementation of the vertical greenery system (VGS) in architecture - Sandra Čekić; Tanja Trkulja; Ljiljana Došenović (Glasnik Šumarskog Fakulteta Univerziteta u Banjoj Luci)
The environmental problems of cities have caused an increase in energy consumption in buildings, which can be slowed by improving the buildings’ energy efficiency. Energy consumption in buildings is affected by the building envelope, and integration of the greenery with the building envelope will contribute in saving energy and increasing the buildings’ energy efficiency. Therefore, the vertical greenery system (VGS) has received a lot of attention in recent decades as a model whose implementation can increase the energy efficiency of buildings. Defining the basic VGS system implementation will allow engineers to systematically approach the process of VGS system implementation and help them choose the best VGS system model for a selected site or building.